2017
DOI: 10.1016/j.jpeds.2017.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Pediatric Mortality from Motor Vehicle Crashes in the United States: A State-Based Analysis

Abstract: Objective To examine geographic variation in motor vehicle crash (MVC)-related pediatric mortality and identify state-level predictors of mortality. Study design Using the 2010–2014 Fatality Analysis Reporting System, we identified passengers <15y involved in fatal MVCs, defined as crashes on U.S. public roads with ≥1 death (adult or pediatric) within 30d. We assessed passenger, driver, vehicle, crash, and state policy characteristics as factors potentially associated with MVC-related pediatric mortality. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 41 publications
1
52
0
Order By: Relevance
“…Children between the ages of 6 and 15, youths and young adult were found to be more vulnerable to fatal road accident compared with both older age groups and infants/pre-school age group (0-5). This finding corroborates the cohort study at the national level by Wolf et al (2017). The reason why children within the ages 6 to 15 were more involved in fatal can be partly related to driver license policy (Romano, Fell, & Voas, 2011).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Children between the ages of 6 and 15, youths and young adult were found to be more vulnerable to fatal road accident compared with both older age groups and infants/pre-school age group (0-5). This finding corroborates the cohort study at the national level by Wolf et al (2017). The reason why children within the ages 6 to 15 were more involved in fatal can be partly related to driver license policy (Romano, Fell, & Voas, 2011).…”
Section: Discussionsupporting
confidence: 85%
“…Earlier studies found no significant difference among race/ethnicity for seat belt usage among Blacks, Whites and Hispanics drivers involved in fatal accident (Daniel, Bladikas, & Curley, 2007;Wells et al, 2002). Study on children (0-15 years) involvement in fatal road traffic accident found that difference in state policy on red-light camera and restraint use had significant influence on risk of fatality in the US (Wolf et al, 2017). There has not been a consistent result of safety measures among race/ethnicity in accident literature.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations